Alocação otimizada de dispositivos indicadores de faltas em linhas aéreas de distribuição utilizando busca em vizinhança variável - Vasconcelos, Jáder de Alencar (2017)
Electricity distribution networks are constantly subject to contingencies that can lead to interruption of supply, bringing disruption to consumers of electric energy and increasing the cost of compensation for violation of individual indicators of continuity. In this context, Fault Indicator Devices (PIs) have been shown to be a promising alternative to improve Quality of Service. As the use of these equipments requires considerable investments, the use of IFs in arbitrary stretches of the network is prohibitive, making necessary the development of a methodology for the optimal allocation of these devices. In this sense, it is understood that a good methodology should minimize the average time of displacement of the maintenance teams to the locations of the defects, implying in the significant reduction of the other indicators dependent on this time, especially the Equivalent Duration of Interruption per Consumer Unit (DEC). The main contribution of this dissertation is the implementation of a meta-heuristic Variable Neighborhood Search (VNS), in order to determine the positions for the installation of the IFs, in order to reduce to the maximum the DEC estimation. In the methodology developed, the chosen network positions (sections) contemplate both the main trunk and the extensions, in addition to considering the influence of other protection devices in the network. In addition, the estimation of the average search time in the presence of these devices considers the failure rates and lengths of the stretches, extending the estimates made in other works. The results, obtained for a real feeder, in most of the studied situations, led to the allocation of IFs in sections of branches, bringing a more significant reduction in the Quality of Service indicators and demonstrating the effectiveness of the proposed methodology.